Culture on Prescription in Portugal: cultural experiences promoting health in lonely people and older adults - Juliana, Louceiro; Carina, Dantas; Natália, Machado; Jana, Eckert; Marcel, Neumann; Christiane, Schlang; Christine H., O’ Kelly; Bart, Borsje (Magyar Gerontológia, 2023)
Social connections play a vital role in personal well-being. Loneliness, characterized by a lack of meaningful social engagement, has emerged as a significant public health concern in Europe, especially after COVID19 pandemic, when the problem was labelled by the media as a “loneliness epidemic” (Berlingieri et al., 2022). According to Casabianca & Kovacic (2022), older adults are especially vulnerable to loneliness due to all the life transitions and disruptive life events they face. Loneliness is more prevalent among Europeans aged 50 and above in southern and eastern regions (ranging from 31% to 46%) compared to western and northern areas (ranging from 10% to 30%).